If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8x + 8) + -5 = -8 + -3x Reorder the terms: -1(8 + 8x) + -5 = -8 + -3x (8 * -1 + 8x * -1) + -5 = -8 + -3x (-8 + -8x) + -5 = -8 + -3x Reorder the terms: -8 + -5 + -8x = -8 + -3x Combine like terms: -8 + -5 = -13 -13 + -8x = -8 + -3x Solving -13 + -8x = -8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -13 + -8x + 3x = -8 + -3x + 3x Combine like terms: -8x + 3x = -5x -13 + -5x = -8 + -3x + 3x Combine like terms: -3x + 3x = 0 -13 + -5x = -8 + 0 -13 + -5x = -8 Add '13' to each side of the equation. -13 + 13 + -5x = -8 + 13 Combine like terms: -13 + 13 = 0 0 + -5x = -8 + 13 -5x = -8 + 13 Combine like terms: -8 + 13 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| -4n-21=-(-6-n)-2 | | 4x^2+3x+0=0 | | 81y^2-8=13 | | -32+5a=-8(a+6)+3 | | 3a-2a-a+11= | | .2x+3=8.6 | | 0=-3x^2+9x+9 | | 3(1-4b)=-6b+33 | | 28-7x=7x-6(2+4x) | | 8x-7=-4x+29 | | a+29=-(4a+3)-8 | | tan(4x+5)=5 | | a+29=-(4a+3)-3 | | 5(x+3)+3x=8 | | -5m=-105 | | -162=-9x | | -15n=-90 | | -754=29x | | 31+(x+44)+(180-4x)=180 | | 5(x+1)=6 | | 4(-r+1)+1=-r+29 | | 31+1d=65 | | 31+1d=50 | | (4x^2+3x-1)-(x^2-6x+8)= | | 3x=3x-21 | | 31+1d=12 | | 4x=9-x | | (x-1)(x+3)=4 | | 167=6+7(2-7x) | | ln(2x+1)+ln(x-1)=lnx | | 0.0058x^2-0.67x+15.2=-3 | | 36i^2+16i+36=0 |